Resistin Associated With Cytokines and Endothelial Cell Adhesion Molecules Is Related to Worse Outcome in COVID-19 - Ebihara, Takeshi; Matsumoto, Hisatake; Matsubara, Tsunehiro; Togami, Yuki; Nakao, Shunichiro; Matsuura, Hiroshi; Onishi, Shinya; Kojima, Takashi; Sugihara, Fuminori; Okuzaki, Daisuke; Hirata, Haruhiko; Yamamura, Hitoshi; et al. (Frontiers in Immunology, 2022)
Introduction: Resistin is reported to form cytokine network and cause endothelial damage. The pathogenesis of coronavirus disease 2019 (COVID-19) were remain unknown but the association of cytokine storm and endothelial damage were crucial. This study aimed to evaluate the resistin in COVID-19 pathogenesis and compared with sepsis. Materials and Methods: First, we evaluated the association of plasma resistin levels and disease severity and clinical outcome in two large cohort; publicly available cohort including 306 COVID-19 patients in the United states (MGH cohort) and our original cohort including only intubated 113 patients in Japan (Osaka cohort 1). Second, to understand pathogenesis, we evaluate resistin, cytokines and endothelial damage markers in COVID-19 and compared with sepsis. Blood sample were collected from 62 ICU treated COVID-19 patients and 38 sepsis patients on day 1 (the day of ICU admission), day 2-3, day 6-8, and from 18 healthy controls (Osaka cohort 2). The plasma resistin, inflammatory cytokines (IL-6, IL-8, MCP-1 and IL-10) and endothelial damage markers (ICAM-1 and VCAM-1) were compared between patients and control. Correlations among resistin, inflammatory cytokines and endothelial damage markers were evaluated in COVID-19 and sepsis. Results: In the MGH cohort, the day 1 resistin levels were associated with disease severity score. The non-survivors showed significantly greater resistin levels than survivors on days 1, 4 and 8. In the Osaka cohort 1, 28-day non-survivors showed significantly higher resistin levels than 28-day survivors on days 6-8. Late recovery (defined as the day of weaning off mechanical ventilation>12 or death) were significantly higher resistin levels than that of early recovery on day 1 and day 6-8. In the Osaka cohort 2, plasma resistin levels were elevated in COVID-19 and sepsis compared to controls on all the measurement points and formed network with inflammatory cytokines and endothelial damage markers. Conclusion: Resistin was elevated in COVID-19 and formed network with cytokines and associated with endothelial damage markers. Higher resistin levels were associated with worse outcome.